Effect of herbivory by goats on primary and secondary metabolism of Cocos nucifera L. (Arecaceae) in a semi-arid environment in Brazilian Northeast - Silva, Nathália Thaís Cavalcante da; Silva, Maria Aline Soares da; Nunes, Alissandra Trajano; Falcão, Hiram Marinho (Journal of Environmental Analysis and Progress, 2020)
The relationship between herbivores and plants has important ecological implications for both organisms and directly affects the plant’s physiological responses, which need to invest in structures and secondary metabolites to overcome the damages. This study aimed to evaluate functional attributes related to the primary and secondary metabolism of Cocos nucifera L. (Arecaceae) submitted to herbivory by goats. Five individuals of C. nucifera were selected in two areas, one with and one without goats. The carbohydrate content, specific leaf mass, and phytochemical screening were obtained, evaluating the presence or absence of saponins, tannins, flavonoids, steroids, alkaloids, and glycosides. The results show that plants under herbivory showed 50% more sugars and a higher specific leaf mass than no-herbivory plants. Also, plants under herbivory showed a higher amount of saponins, steroids, and alkaloids. The production of defense metabolites, which are energetically costly, require the energy supply provided by the carbohydrates produced in photosynthesis; thus, higher levels of sugars were observed in attacked plants. Even under attack, C. nucifera plants allocate resources for biomass production, to increase leaf sclerophylly and hinder herbivory. The investment in saponins, steroids, and alkaloids is related to herbivory, as demonstrated by the analysis of principal components analysis. We conclude that herbivory by goats activates defense responses in C. nucifera plants, making them allocate sugars to produce secondary metabolites.